Handbook of algal technologies and phytochemicals. Volume II, Phycoremediation, biofuels and global biomass production - Ravishankar, Gokare A.; Ranga Rao, Ambati (Boca Raton, FL : CRC Press, 2020)
Key Features The most comprehensive resource available on the biodiversity of algal species, their industrial production processes and their use for human consumption in food, health and varied applications. Emphasis on basic and applied research, addressing aspects of scale-up for commercial exploitation for the development of novel phytochemicals (phytochemicals from algae). Addresses the underexplored and underutilized potential of chemicals from marine sources for health benefits. Each chapter, written by expert contributors from around the world, includes a Dictionary of Terms, Key Facts, Summary Points, Figures and Tables, as well as up-to-date references. The second book in this two-volume set explores phycoremedation applications, and the sustainable use of algae for biofuels and other products of economic value. It also looks at aspects such as macro- and micro algal impact on marine ecosystem and remote sensing of algal blooms. The commercial value of chemicals of value to food and health is about $6 billion annually, of which 30 percent relates to micro and macro algal metabolites and products for health food applications. As a whole, the two volumes explore the aspects of diversity of micro and macro algal forms, their traditional uses; their constituents which are of value for food, feed, specialty chemicals, bioactive compounds for novel applications, and bioenergy molecules. Bio-business and the market share of algae-based products are also dealt with, providing global perspectives.
OCLC-licensed vendor bibliographic record.
Keywords: Algae products; Algae -- Biotechnology; SCIENCE / Life Sciences / Biology / Marine Biology; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General